From a lag in vector activity to a constant increase of translocations: invasion of Callosciurus squirrels in Argentina - Guichon, Maria Laura (2015)
Arboreal squirrels of the Asiatic genus Callosciurus have shown high likelihood of establishment from few released animals, in particular, C. erythraeus has established wild populations in Argentina, Belgium, France, Hong Kong, Japan, and The Netherlands. We report the invasion process of C. erythraeus in Argentina in the last four decades and suggest management actions for each foci. Between February 2011 and November 2014 we conducted field surveys and interviews in nine sites in central Argentina to confirm the presence of C. erythraeus, describe their history of introduction, and estimate range expansion and squirrel relative abundance. We report a two decades lag-phase until the onset of translocations of C. erythraeus within national boundaries that resulted in a constant increase of the cumulative number of releases. We confirm nine new release events between 1995 and 2012 and six new invasion foci that yields a total of 13 deliberate releases and 10 invasion foci established in rural and urban areas of Argentina. Spread rate ranged from 0.12 to 0.66 km/year. An intermediate relative density of squirrels (2–7 ind/ha) was found close to release sites except in one case. All introduction events involved squirrels translocated from the first, 40 years old invasion focus, occasionally involving illegal trade. The rate of introduction events in the last decades and the translocation-lag phase described in this study should call the attention in all countries dealing with charismatic, introduced species. Translocation disruption requires urgent attention to slow down the invasion of this and other species.